Unveiling the Powers of the ICC Prosecutor: Promoting Access to Justice and Accountability through Sustainable Development Goal 16 - Oyewole, Oriola O. (Journal of Sustainable Development Law and Policy, 2024)
Criminal prosecution, as one of the transitional justice mechanisms, aims to address the legacies of serious human rights violations and international humanitarian law. The mandate of the International Criminal Court (ICC) is to bring perpetrators of atrocity crimes to justice by initiating investigations, issuing arrest warrants and conducting criminal trials. At the heart of ICC’s mandate is the Prosecutor, whose powers are indispensable for achieving peace, access to justice and accountability in the international community. Sustainable Development Goal16 (SDG 16) is characterised by its focus on nurturing peaceful and inclusive societies, ensuring access to justice, and strengthening effective institutions. This paper explores the intersection of SDG16 with the discretionary powers vested in the ICC Prosecutor in investigating and prosecuting atrocity crimes. Employing a doctrinal approach, it critically examines legal frameworks, principles, and case precedents to unravel the intricacies and implications of prosecutorial discretion. The paper reveals the diverse array of influences that guide the ICC Prosecutor’s selection of situations and cases, encompassing legal and extra-legal considerations. Notably, the paper emphasises the substantial impact of the ICC Prosecutor’s discretionary powers on the advancement of SDG16, particularly in investigations, case prioritisation, and collaboration with national jurisdictions. Furthermore, the paper recommends proactive cooperation and positive complementarity among states to effectively realise the objectives of SDG 16.